1992
DOI: 10.1002/ajmg.1320430321
|View full text |Cite
|
Sign up to set email alerts
|

Additional case of neuhäuser megalocornea and mental retardation syndrome with congenital hypotonia

Abstract: We report on a 3-1/2-year-old Spanish girl with the Neuhäuser megalocornea and mental retardation syndrome. A review shows that megalocornea, mental retardation, and, presumably, hypotonia, are the major manifestations for diagnosis. The facial appearance of the typical cases is characterised by frontal bossing, broad nasal bridge, mild hypertelorism, long upper lip, and small mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Since the original report (Neuh~iuser et al, 1975), 24 cases of the MMR syndrome have been reported including the present case (Frank et al, 1973;Schmidt and Rapin, 1981;Del Guidice et aL, 1987;GrCnbech-Jensen, 1989;Frydman et al, 1990;Kimura et al, 1991;Temtamy et al, 1991;Santolaya et aL, 1992;Verloes et al, 1993;Antifiolo et aL, 1994). Frequency of the clinical findings seen in these cases are summarized (Table 1).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Since the original report (Neuh~iuser et al, 1975), 24 cases of the MMR syndrome have been reported including the present case (Frank et al, 1973;Schmidt and Rapin, 1981;Del Guidice et aL, 1987;GrCnbech-Jensen, 1989;Frydman et al, 1990;Kimura et al, 1991;Temtamy et al, 1991;Santolaya et aL, 1992;Verloes et al, 1993;Antifiolo et aL, 1994). Frequency of the clinical findings seen in these cases are summarized (Table 1).…”
Section: Discussionmentioning
confidence: 69%
“…In the megalocornea-mental retardation (MMR) syndrome, megalocornea is associated with mental retardation, hypotonia and minor anomalies. So far, since first description of the MMR syndrome (Neuh~iuser et al, 1975), about 23 cases have been reported (Frank et al, 1973;Schmidt and Rapin, 1981;Del Guidice et al, 1987;GrCnbech-Jensen, 1989;Frydman et al, 1990;Kimura et aL, 1991;Temtamy et aL, 1991;Santolaya et al, 1992;Verloes et al, 1993;Antifiolo et al, 1994). A subclassification of the MMR syndrome due to presumed genetic heterogeneity has been proposed (Verloes et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Temtamy et al [1991] reported on 3 similar pa tients, and suggested the name megalocornea-mental retardation-2 (MMR-2). The designation MMR-1 should be reserved for the syndrome first described by Neuhauser et aL [1975] and subsequently by others [Schmidt and Rapin, 1981;Del Giudice et al, 1987;Gronbech-Jensen, 1989;Santolaya et al, 1992], Santolay a et al [1992] included the patient reported by Frank et al [1973] in their overview of patients with the MMR-1 syndrome. However, Raas-Rothschild et al [1988] argued that the Frank et al case [1973] does not fit into the description of the MMR-1 syndrome, for which they recommended the eponym of Neuhauser syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Major features of the Neuhauser syndrome are mental retardation, megalocornea and hypotonia (Frank et al, 1973;Neuhauser et al, 1975;Schmidt and Rapin, 1981;Del Giudice et al, 1987;Raas-Rothschild et al, 1988;Gronbech-Jensen, 1989;Frydman et al, 1990;Temtamy et al, 1991;Santolaya et al, 1992;Verloes et al, 1993;Balci et al, 2002). Megalocornea is a developmental defect of the eye characterized by a nonprogressive and symmetrical enlargement of the cornea in the absence of elevated intraocular pressure, and should be differentiated from congenital glaucoma and anterior megalophthalmos (Laibson and Rapuano, 1998).…”
Section: Discussionmentioning
confidence: 97%